Electroluminescence of a device based on europium beta-diketonate with phosphine oxide complex - Quirino, W. G.; Adati, R. D.; Lima, S. A. M.; Legnani, C.; Jafelicci, M.; Davolos, Marian Rosaly [UNESP]; Cremona, M. (Elsevier B.V., 2006)
Rare earth (RE) ions have spectroscopic characteristics to emit light in narrow lines, which makes RE complexes with organic ligands candidates for full color OLED (Organic Light Emitting Diode) applications. In particular, beta-diketone rare earth (RE(3+)) complexes show high fluorescence emission efficiency due to the high absorption coefficient of the beta-diketone and energy transfer to the central ion. In this work, the fabrication and the electroluminescent properties of devices containing a double and triple-layer OLED using a new beta-diketone complex, [Eu(bmdm)(3)(tppo)(2)], as transporting and emitting layers are compared and discussed. The double and triple-layer devices based on this complex present the following configurations respectively: device 1: ITO/TPD (40 nm)/[Eu(bmdm)(3)(tppo)(2)] (40 nm)/Al (150 nm); device 2: ITO/TPD (40 nm)/[Eu(bmdm)(3) (tppo)(2)] (40 nm)/Alq(3) (20 nm)/Al (150 nm) and device 3: ITO/TPD (40 nm)/bmdm-ligand (40 nm)/Al (150 nm), were TPD is (N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1-biphenil-4,4-diamine) and bmdm is butyl methoxy-dibenzoyl-methane. All the films were deposited by thermal evaporation carried out in a high vacuum system. These devices exhibit high intensity photo- (PL) and electro-luminescent (EL) emission. Electroluminescence spectra show emission from Eu(3+) ions attributed to the (5)D(0) to (7)F(J) (J = 0, 1, 2, 3 and 4) transitions with the hypersensitive (5)D(o) -> (7)F(2) transition (around 612 nm) as the most prominent one. Moreover, a transition from (5)D(1) to (7)F(1) is also observed around 538 nm. The OLED light emission was almost linear with the current density. The EL CIE chromaticity coordinates (X = 0.66 and Y = 0.33) show the dominant wavelength, lambda(d) = 609 nm, and the color gamut achieved by this device is 0.99 in the CIE color space. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: rare earth complexes; electroluminescence; energy transfer; beta-diketones